The effect of falciparum malaria prevalence on the effectiveness of intermittent preventive treatment with Sulfadoxine-Pyrimethamine during pregnancy in reducing low birth weight in southern Mozambique - Rheeder, Paul (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.